A natureza das estruturas globais de argumentação e avaliação do argumento de prova em um contexto de ensino baseado em resolução de problemas e programação em blocos - Rodrigues, Fredy Coelho (Universidade Estadual Paulista (Unesp), 2025)
This study initially aims to investigate the nature and anatomical design of the “global design of the “global argumentation structures” that emerge from a teaching context based on teaching context based on problem solving in a block programming environment - Scratch. Scratch. Secondly, the aim is to assess the quality and soundness of the argument used at the end of the argumentative process. The study presented here, was proposed to be carried out at IFSULDEMINAS, Campus Passos and the subjects of the research are students entering the Mathematics degree course at the IFSULDEMINAS in Mathematics at this institution in 2024 and 2025. Based on the objectives proposed in this investigation, the following research questions were outlined a) what global argumentation structures emerge from the reasoning used by the students investigated during the by the students investigated during the process of collective argumentation and proof? b) How does the teacher how does the teacher participating in collective argumentation support/shape the emergence of these structures? c) how do the students under investigation argue to validate mathematical ideas and conjectures? conjectures? The study is justified in that it aims to deepen the discussion and understanding of the subject, exploring new results and corollaries resulting from Rodrigues' doctoral thesis (2023). To this end, it is proposed to carry out a case study (exploratory/descriptive/explanatory) in order to better understand the phenomenon involving “situations of collective argumentation in a teaching context based on based on problem solving in a block programming environment”. The proposed case study was structured in three phases. The first phase involves bibliographical research on the subject, as well as a training course training course to provide the subjects taking part in the research with tools for handling and media production in the Scratch programming environment. In the 2nd phase, it is proposed to solving problems involving the theme “numerical properties and functions” in the environment (Scratch). In this phase, data will be collected by videotaping of the oral arguments generated by the group work, as well as by group work as well as by collecting the file containing the lines of programming involved in solving the problem. In the 3rd phase, the data will be analyzed based on the anatomical model of the global structures of argumentation as well as through the evaluation model of the proof argument. As a result of this study, it is hoped that can provide new corollaries arising from the results of the thesis study by Rodrigues (2023).
La nature des structures globales d'argumentation et d'évaluation des arguments de preuve dans un contexte pédagogique basé sur la résolution de problèmes et la programmation par blocs
Keywords: Argumentação; Programação em blocos; Argumento de prova; Resolução de problemas; Argumentação matemática